Vliyanie aminalona i pikamilona na rabotosposobnost akrobatov pri obuchenii uprazhneniyam "gorizontalnyj upor nogi vroz" i "Rondat - salto nazad" - Mandrikov, V. P.; Lihodeeva, V. A.; Spasov, A. A.; Kuchkin, S. N.; Antsyperov, V. V.; Chizhikov, A. M. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of this research was to study the influence of aminalon and picaminalon on the development of the acrobatic exercises "horizontal thrust - legs separately" and "rondat - somersault back". 40 boys-acrobats aged 10-12 were participated in the research. The use of preparations of neurometabolic action such as aminalon and picaminalon, influencing on the growth of the activity of the central mechanisms of regulation, had the positive effect on the formation and fastening of the adaptive skills getting the strongly pronounced selective orientation, caused by the motor specificity of an exercise, and also promoted an effective utilization of the real motor and static potentials of young athletes.